Enhancing Forest Fire Mitigation through Communication Technology: Evidence from Riau Province, Indonesia - Firsa Rinaldy Parlita Tinambunan; Miftahul Rozaq (Eduvest - Journal of Universal Studies, 2025)
Forest and land fires (karhutla) in Riau Province, Indonesia, pose severe environmental, health, and economic challenges, mainly due to the flammable peatlands during dry seasons. Limited communication infrastructure exacerbates these issues, hindering firefighting coordination, hotspot reporting, and public information dissemination. This study examines the role of communication technology in mitigating karhutla, focusing on the Ministry of Environment and Forestry's efforts in Riau. Using a qualitative case study approach, data was collected through interviews and analysed thematically. Findings reveal inadequate communication technology support, with reliance on Handy Talky (HT) devices and radio transmissions, while cellular and internet networks remain insufficient. The study recommends enhancing communication infrastructure, developing integrated systems, and training personnel to address these challenges. Satellite-based internet is proposed as a potential solution for areas with limited connectivity, aiming to improve coordination and efficiency in karhutla mitigation efforts.